2020
DOI: 10.1116/6.0000244
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of thin silver film growth on weakly interacting silicon dioxide substrates using oxygen as a surfactant

Abstract: Manipulation of thin silver film growth on weakly-interacting silicon dioxide substrates using oxygen as a surfactant Running title: Manipulation of thin silver film growth on weakly-interacting silicon dioxide substrates using oxygen as a surfactant

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 75 publications
(78 reference statements)
2
19
0
Order By: Relevance
“…Hence our findings indicate strongly that alloying agents lead to flatter film formation by hindering island reshaping during coalescence, in agreement with our previous studies 62,63 and recent literature reports. 73 However, we note that other mechanisms, including increase of island density during nucleation 23,24 and/or suppression of upward mass transport during island growth (the latter suggested by McDougall et al 74 for explaining formation of bilayer Dy films on graphene well below room temperature), may also be contributing factors to the observed morphological evolution.…”
Section: Layersupporting
confidence: 93%
See 2 more Smart Citations
“…Hence our findings indicate strongly that alloying agents lead to flatter film formation by hindering island reshaping during coalescence, in agreement with our previous studies 62,63 and recent literature reports. 73 However, we note that other mechanisms, including increase of island density during nucleation 23,24 and/or suppression of upward mass transport during island growth (the latter suggested by McDougall et al 74 for explaining formation of bilayer Dy films on graphene well below room temperature), may also be contributing factors to the observed morphological evolution.…”
Section: Layersupporting
confidence: 93%
“…This is achieved using spectroscopic ellipsometry, a nondestructive optical technique that determines the optical properties of materials by measuring changes in the polarization state of a light beam upon its interaction with the sample under investigation. 67 The methodology used for collecting and analyzing ellipsometric data has been explained in detail in our previous studies, [61][62][63][64] hence here we only summarize key aspects.…”
Section: B In Situ Film Growth Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…This effect is found to be enhanced by the steady supply of mobile atoms from the vapor phase, although it can also be halted if the deposition rate is too fast, and in this case the cluster equilibrates via material agglomeration. Thus, careful control of the vapor flux temporal profile during the coalescence stage of film growth [28], as well as direct inhibition of 2D layer migration by deploying minority species at the growth front [146][147][148], are potentially promising strategies for promoting 2D growth morphology. Moreover, the analytical model developed in Paper 3 may serve as the basis for expanding film growth theories by incorporating descriptions of the equilibration dynamics of faceted 3D islands, while it helps to explain inconsistencies between theoretical and experimental reports with regards to film growth dynamics.…”
Section: Chapter 4 Contribution To the Field And Outlookmentioning
confidence: 99%
“…Pliatsikas et al studied the surface morphological evolution of magnetron-sputtered thin silver films deposited on silicon dioxide substrates, and found that silver layers grow flatter in the oxygen-containing gas atmosphere due to incomplete island coalescence. However, they also found that oxygen causes the increase of electrical resistivity of the silver layers [ 15 ]. Wang et al provided an effective method for the fabrication of transparent silver electrodes and found that minimal oxygen-doping significantly improves the optical and electrical performances of silver films [ 16 ].…”
Section: Introductionmentioning
confidence: 99%